Students’ writing skills through collaborative writing and the tendency to work in a group - Afrezah, Novela Nur; Azizi, Meirita Rahmi; Alrian, Rahmad; Pratiwi, Dwiyani; Yulia, Yuyun (Univeritas Papua, 2024)
This study aims to enhance students' writing skills through collaborative writing at a Senior High School and determine their preference between collaborative writing in pairs or groups. The study discovered that students lacked enthusiasm in completing the writing work, which caused poor motivation and challenges in formulating ideas. This study employed a classroom action research (CAR) methodology and consisted of two cycles. The data were collected through observations of the teaching and learning process, interviews with students, and conducting writing assessments. The research findings indicated that engaging in collaborative writing increased students' interest in writing activities due to the opportunity for interaction with their peers. Collaborative writing facilitated the creation of ideas by allowing each group member to contribute, resulting in a diverse range of thoughts. The successful implementation of collaborative writing was complemented by the implementation of group work. It was also shown that students prefer collaborating more in group tasks than working in pairs. The researcher discovered an enhancement in the students' writing scores.